Evaluation of microleakage of Ionoseal filling material as a fissure sealant agent - Effat Khodadadi; Behnaz Esmaeili; Naemeh Karimian; Soraya Khafri (Babol University of Medical Sciences, 2014)
Introduction: Sealing pits and fissures was introduced as an approach to prevent occlusal caries for more than two decades. The aim of this study was to compare the microleakage of flow able resin reinforced glass ionomer (Ionoseal) with other materials used as fissure sealants. Methods: In this in vitro study, 50 premolar teeth of human free of any caries were selected. Fissurotomy was done with fissure bur. The samples were randomly categorized into five groups (Fissurit FX, Fuji II light-cured,Grandio flow, Ionoseal). Ionoseal was assessed by using two methods: with and without etching and bonding agent prior to sealant application. After sealant placement, all surfaces of the teeth except 2 mm area around the sealant margins were covered with two layers of nail polish.The specimens were thermocycled, and they were sectioned after immersing into a 0.5 % basic fuchsine solution. The amount of microleakage was examined by stereomicroscope. Results: The microleakage comparisons of groups indicated that Ionoseal without etching and bonding application had significantly greater microleakage than the other groups (p<0.001), while there was statistically no significant difference between the microleakage of Ionoseal and the other groups after etching and bonding application (p>0.05). Conclusions: By considering isolation difficulties in children and observing high amount of Ionoseal microleakage (without etching and bonding application), the samples need to be etched and bonded like other resin-based materials before Ionoseal placement in order to achieve clinically desirable microleakage outcomes.